Annual Plan 1967-68 Government of Andhra Pradesh Planning Department - Planning Commission (Planning Commission, 1967)
State plan-summary, state plan-details of schemes, state plan-(contd), training centres, minor irrigation, soil conservation, khadi and village industries, public health, housing, broadcasting, centrally sponsored schemes
Government of Andhra Pradesh Planning Department